Big Little Monkey - Schaefer, Carole Lexa (Candlewick Press, 2008)
When Little Monkey decides to venture out into the jungle alone, beyond the gaze of his watchful Mama, he discovers that other animals are not as friendly and warm as his own family and that independence is not altogether a good thing.